THE CHRONOTOPES IN BORCHE PANOV’S LYRICAL POEM TITLED “MICHELANGELO” - Trajkovska, Daniela Andonovska (PALIMPSEST / ПАЛИМПСЕСТ, 2019)
The aim of this research is to conduct a hermeneutic and aesthetic analysis of Borche Panov’s lyrical poem, titled “Michelangelo” (Panov, 2014). The hermeneutic analysis in this context has no theological backing and is not a sum of methodological procedures intended to unravel the unique and the only possible meaning of the text. On the contrary, the analysis is done in the light of the theories of Heidegger, Gadamer and Bakhtin. The analysis is, in fact, aimed at disclosing several likely interpretations of the poem from the perspective of the phenomenology of human existence, perceived through language, and directed towards elucidating the chronotope of the human being, i.e. the chronotope of the light. Given that the title and the content of the poem make an explicit reference to the famed Renaissance poet, Michelangelo, the aim is to determine the way in which that extra-textual connection is established, or in other words, to inspect how the language in the lyrical poem functions and makes the interpretation possible.